Respuesta :

Answer:

Step-by-step explanation:

Let's solve your equation step-by-step.

−31

2

b+

2

3

=

51

4

+

5

6

b

Step 1: Simplify both sides of the equation.

−31

2

b+

2

3

=

5

6

b+

51

4

Step 2: Subtract 5/6b from both sides.

−31

2

b+

2

3

5

6

b=

5

6

b+

51

4

5

6

b

−49

3

b+

2

3

=

51

4

Step 3: Subtract 2/3 from both sides.

−49

3

b+

2

3

2

3

=

51

4

2

3

−49

3

b=

145

12

Step 4: Multiply both sides by 3/(-49).

(

3

−49

)*(

−49

3

b)=(

3

−49

)*(

145

12

)

b=

−145

196

Answer:

b=

−145

196